A New Dimension of “Self-Other” Category in Joseph Conrad’s “The Secret Agent” - Костенко, Ганна Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article investigates J. Conrad’s first “English” novel distinguished by its new themes and problems, as well as its particular structure and time category interpretation. The novel’s key theme is focused on the question of foreignness which generally remains beyond the researchers’ interests, and this fact proves the topicality of investigation. Moreover, people’s foreignness turns into a moral category which overcomes national and cultural differences making people stronger (like in case of Michaelis and his patroness), but sometimes vulnerable in their humanity (like in case of Stevie). “Foreignness” permeates J. Conrad’s work from inside raising the “Self-Other” dilemma to a new ideological level, not as people’s difference by cultural and national features, but as an opposition of different moral dogmas, and this approach requires further systematization.